1997
DOI: 10.1038/bjc.1997.120
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the circulating level of hepatocyte growth factor in gastric cancer patients

Abstract: Summary We measured serum concentrations of hapatocyte growth factor (HGF) in patients with gastric cancer and compared these with the histological findings and conventional tumour markers, including CEA, CA19-9 and CA125, for evaluation of the significance of serum HGF levels as a tumour marker. The HGF levels were measured by an enzyme-linked immunosorbent assay (ELISA) system. The average levels of serum HGF in 89 healthy control subjects, 104 patients with primary gastric cancer and 15 patients with recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…Several investigators reported that serum HGF levels in cancer patients were increased significantly when compared with those in healthy volunteers. [21][22][23] Serum HGF levels in the patients were reported to be affected by liver injury or renal disease. 35,36 All of the patients included in this experiment showed normal liver function and kidney function, however, and did not exhibit any severe inflammation of other organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators reported that serum HGF levels in cancer patients were increased significantly when compared with those in healthy volunteers. [21][22][23] Serum HGF levels in the patients were reported to be affected by liver injury or renal disease. 35,36 All of the patients included in this experiment showed normal liver function and kidney function, however, and did not exhibit any severe inflammation of other organs.…”
Section: Discussionmentioning
confidence: 99%
“…18 It was reported that HGF induced tyrosine phosphorylation of focal adhesion kinase, p125FAK, 19 and promoted the migration and invasion of oral SCC cells. 20 Moreover, in several clinical studies, a relationship between the concentration of HGF in serum or in cancer tissue and the progression of disease has been noted in patients with gastric cancer, 21 breast cancer 22 and lung cancer, 23 but has not been reported in patients with oral cancer.…”
mentioning
confidence: 99%
“…Yu et al recently showed that a nonautocrine interaction between HGF transgenic hosts and c-Met expressing melanoma cells significantly promotes tumor metastasis in vivo (Yu and Merlino, 2002). Clinically, elevated serum HGF levels have been found in patients with cancers from bladder, breast, colon, gastric, liver, lung and head and neck (Takigawa et al, 1997;Taniguchi et al, 1997;Fukuura et al, 1998;Toi et al, 1998;Junbo et al, 1999;Gohji et al, 2000;Naughton et al, 2001;Uchida et al, 2001, Dong, 2001b. Significantly, this elevated serum HGF is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum HGF concentrations have been reported to be elevated in liver disease, chronic renal failure, systemic inflammatory response syndrome (SIRS), and malignant diseases such as leukemia, breast cancer, and gastric cancer. [17][18][19][20] Circulating HGF is increased in the presence of septic complications. Sakon et al 21 reported that HGF in serum was elevated in patients with sepsis, and also correlated with CRP in patients with nonseptic SIRS.…”
Section: Discussionmentioning
confidence: 99%